The development of the lung metastatic niche in murine breast cancer - Lin, SS (2023)
Cancer metastasis causes 90% of cancer deaths. Patients with secondary lung metastases often show only modest responses to chemotherapy, immunotherapy, and anti angiogenic therapy, and can develop resistance. Remodelling of the metastatic niche and the use of alternative, non-angiogenic, vascularisation pathways such as vessel co-option are thought to contribute to resistance to therapies. However, there is only limited knowledge about the molecular mechanism underlying metastatic niche formation, and the expression profile of genes driving tumour vessel co-option is poorly understood. In part, this is due to the paucity of in vitro and in vivo models that accurately recapitulate the metastatic niche in human cancers. Here, I developed a preclinical E0771 breast cancer (BC) lung metastasis mouse model with which I investigated tumour vessel development and the metastatic niche. First, MRI imaging and histological assessments were used to study vessel growth patterns, suggesting the predominant use of vessel co-option by metastases at an early stage of development, while the induction of angiogenesis was seen during the progression to subpleural metastases. Next, I combined metastatic niche labelling with single-cell RNA sequencing (scRNA-seq) to study the transcriptome of the stroma during metastatic progression. This analysis detected a shift in endothelial cell (EC) subtypes between early and late metastatic timepoints. Interestingly, co-opted capillaries were found to enhance their OXPHOS-related genes and downregulate genes linked to tight junctions, suggesting a hyperpermeability response that may facilitate tumour cell extravasation. Further analysis of this scRNA-seq data also identified cancer-associated mesenchymal cells (CAMCs) in the late metastatic niche, which acted as the primary source of the pro-angiogenic factor VEGFA. Lineage tracing analysis using Wt1-CreERT2;tdTomato reporter mice also examined whether pleural mesothelial cells exhibited pro-metastatic capacity, but suggested that they had little capacity, migrating only underneath the subpleura and few co-expressed CAMC markers. This finding was supported by the scRNA-seq data, which suggested that pleural mesothelial cells partially contribute to the growth of the subpleural metastases but were not the primary origin of the CAMC subtypes. In conclusion, analysis of this preclinical lung metastasis model has enabled me to demonstrate the temporal and spatial heterogeneity present within the metastatic niche and distal cells, and to interrogate the gene expression patterns involved in vessel co-opting and angiogenic metastases. This data could provide important information when selecting vascular drugs to target early vs late metastasis, whilst this extensive transcriptome dataset of lung stromal cells in the metastatic niche and distal regions can provide a basis for further research into the mechanisms involved.